Análise da qualidade de vida na aglomeração urbana de Araçatuba-SP : uma proposta metodológica com a utilização de Sistemas de Informação Geográfica (SIGs) - Gomes, Márcio Fernando (2016)
From the second half of the twentieth century Brazil is going through an intense and accelerated process of urbanization. Urban sprawl and the lack of proper planning led to the deterioration of cities, environmental and social impacts that directly affect the quality of life of city dwellers. Given this context, this research has the general objective to develop a methodology to analyze the quality of urban life from the spatial distribution of indicators related to infrastructure, public services and environmental quality, and the use of Information Systems geographic (GIS). To evaluate the quality of urban life the following indicators were considered: water supply, sewage, garbage collection, road paving, health facilities, educational institutions, public transport, free of flood areas, vegetation cover and open spaces and areas leisure. The methodology for the analysis of quality of life was applied in the Urban Agglomeration of Araçatuba-SP (AUA). The use of Geographic Information Systems (GIS) has proven an effective tool in spatial analysis of the quality of urban life. The SIGs allowed the insertion, storage, integration, data handling and the graphical representation of spatial information related to the selected indicators for the analysis of quality of life. The Quality of City Life Index (IQVU) showed similar values in the cities of the Agglomeration Aracatuba Urbana. Analyzing the spatial distribution of IQVU within the cities of Agglomeration Araçatuba City it can be said that, in general, the quality of life tends to be higher in sectors located near the central area, is gradually falling toward periphery and reaches the worst rates in the transition areas between urban and rural areas.